1999
DOI: 10.1159/000016529
|View full text |Cite
|
Sign up to set email alerts
|

The Remineralization of EDTA–Treated Human Dentine

Abstract: The remineralization of whole human dentine treated with a neutral EDTA solution was investigated: the treatment periods were 15, 30 and 120 min. From the literature it is known that EDTA removes noncollagenous proteins (NCPs) from dentine powders. In order to extract more phosphoproteins from dentine lesions, in part of this work samples were also treated with 1 M NaCl or 4 M guanidine chloride solutions. All the dentine samples after the treatments mentioned were immersed subsequently in a remineralizing sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 15 publications
3
49
0
5
Order By: Relevance
“…There was a concern that no direct comparison was performed between 30-s immersion and 24-h immersion in the Control group. It should be noted that the immersion of EDTA-demineralized dentin in artificial saliva for up to several days or weeks did not induce remineralization [31][32][33] . On the other hand, there is a study revealed that demineralized dentin immersed in artificial saliva for up to 21 days showed constant (slight) activity of endogenous collagenases, comparing to 1-day immersion 34) .…”
Section: Discussionmentioning
confidence: 95%
“…There was a concern that no direct comparison was performed between 30-s immersion and 24-h immersion in the Control group. It should be noted that the immersion of EDTA-demineralized dentin in artificial saliva for up to several days or weeks did not induce remineralization [31][32][33] . On the other hand, there is a study revealed that demineralized dentin immersed in artificial saliva for up to 21 days showed constant (slight) activity of endogenous collagenases, comparing to 1-day immersion 34) .…”
Section: Discussionmentioning
confidence: 95%
“…The prolonged application of EDTA resulted in a similar decrease of the CS, confirming previous data on the ability of EDTA to remove dentin noncollagenous proteins. 36 It has been demonstrated previously that because of its high affinity with water, CS morphologic status depends on the tissue hydration level. 16 Thus we can hypothesize that phosphoric acid, which draws water from the tissue because of its osmolarity, 18 greatly affects the three-dimensional status of CS.…”
Section: Discussionmentioning
confidence: 99%
“…Dentin remineralization by STMP associated with a calcium solution by the formation of calcium phosphate crystals was previously reported [Zhang et al, 2012] and is also supported by our results. The combination of STMP with calcium hydroxide (Ca(OH) 2 ) might also favor dentin remineralization by the formation of a calcium phosphate precursor that promotes conditions for mineral crystal growth required for remineralization [Kawasaki et al, 1999;Featherstone, 2000]. The phosphorylation of proteins present on the surface of an organic template by STMP could trap calcium ions by electrostatic force resulting in prenucleation clusters [Wang et al, 2001;George and Veis, 2008].…”
Section: Discussionmentioning
confidence: 99%